Rancangan Perbandingan Pelebaran Perkerasan Jalan Lentur Dengan Metode Bina Marga 1987 dan Bina Marga 2017 Pada Ruas Jalan Semarang – Purwodadi di Kecamatan Tegowanu Pada STA 25+700 – STA 27+700 - Ni'am, Muhammad Choirul; Fajar Budi Prasetyo, Reno Martin; Husodo, Ibnu Toto; Budirahardjo, Slamet (Jurnal Teknik Sipil Giratory UPGRIS, 2022)
ABSTRACTThe road is a means of transportation that then develops into a means of transportation in carrying out economic activities both accessibility and mobility of goods and services. Heavy traffic and violations on road users and owners of large vehicles passing through often make construction on road pavements damaged.Road widening is one of the main structures in road construction where the construction system is required to be able to provide safety and comfort for its users. Factors that affect the performance of road pavements are passing traffic, weather, pavement layer design, as well as maintenance.In this study, an analysis was carried out for thick layers of road pavement using the Bina Marga Component Analysis Method 1987 and the Bina Marga Method 2017 so that later it would be obtained a thick layer of pavement according to needs. CBR data is obtained from field DCP results conducted by self-testing. For the planned plan life of 20 years, the traffic growth rate is 4.4% and the functional classification of the road is a collector's road.From the results of calculations obtained each thickness of the flexible pavement layer, namely: Bina Marga Component Analysis Method 1987 has a layer value of D1 = 10 cm, D2 = 20 cm, D3 = 30 cm as well as the Bina Marga Method 2017 has a layer value of D1 = 8.75 cm, 15 = cm, D3 = 15 cmKeywords: Road Widening, Component Analysis 1987, Bina Marga 2017